More than opportunistic victims: the multiple profiles of Chinese urban nail households. - Li, Chen; Day, Jennifer; Wang, Mark (International Development Planning Review, 2019)
This research describes the initiation, bargaining and outcome stages of conflict that occur for nail households who resist housing demolition and relocation in urban China. Across the three stages, we describe four profiles that nail households demonstrate as they bargain for compensation terms: hard, hardened, softened and soft. These four profiles display different resistance trajectories and modes, emerging as nail households with various motivations and at different points of conflict, employing various and changing strategies in response to the bargaining process and thereby arriving at various ultimate outcomes in the bargaining process. The outcome for the nail households is a product of the initial mode of resistance used, the power held by the nail households, the emergent strategies that households adopt as the conflict develops, and other internal and external factors. The particular process provides a suite of tools to deepen our understanding of nail households and their conflicts with local governments and private developers in urban China.